Enhancing Heavy-Vehicle Safety Utilizing Proximity Sensor and Microcontroller for Proactive Blind Spot Detection - Zulfa, Bilqisthi Ananda; Hersyah, Mohammad Hafiz (Universitas Andalas, 2026)
While Heavy Goods Vehicles (HGVs) are essential to the global economy, their massive size creates dangerous visibility gaps, or